Diagnóstico turístico de la parroquia Febres Cordero según los factores que influyen su desarrollo - Moreira Quinaloa, Vicky Alexandra (2020)
Tourism has always been one of the important elements in the economy of the villages, therefore, it is important to consider this case study that aims to identify the factors that influence the tourism development of the Febres Cordero parish in the province of Los Rivers, for this case it was established to carry out a diagnosis in the area in order to determine the conditioning variables for the tourist impulse in the area. An inductive and deductive methodology was used, as well as the description of tourist sites of the Febres Cordero Parish, in addition the bibliographic method was used to support the information contained; techniques were used such as the observation of the factors of the place and the interview with GAD officials of the Febres Cordero parish, as well as the inhabitants of different enclosures and tourists who come to the area. Among the main findings was the absence of a tourism promotion plan, the lack of accessibility to possible attractions, citizen insecurity and the limited dissemination of their management holidays. Among the main solutions is the improvement of the access roads to the tourist sites of the Parish, the placement of respective signage in the areas, construction of trails, the conditioning of cabins and accommodation sites, in order to promote better infrastructure, police security and protection; but above all to offer more frequent festivals of gastronomy and influx of tourists to the Febres Cordero Parish.